Teaching Reading with Collaborative Learning: An Experiment Study in SMPN 4 Busungbiu - Kadek Mawar Sopiani; Ni Made Ratminingsih; I Nyoman Pasek Hadi Saputra (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This study aimed to analyze the use of collaborative learning method in teaching reading on the EFL students at SMPN 4 Busungbiu in online learning and analyzed the teacher difficulties in implement the collaborative learning method. This study was qualitative research to explore the specified phenomenon. The subjects in this study were an English teacher and the ninth grade A students and ninth grade C students. The instruments were observation sheet, and interview guide. The data were collected by take a note, observation, and record the teacher’s answer from the interview. The collected data have been analyzed descriptively. The result of this study showed that the use of collaborative learning method by the teacher in reading activities through online learning has been carried out through pre activity, whilst activity and post activity. The result of observation also showed that the result of students ‘abilities were more improved after the collaborative learning method was carried out after the collaborative learning method did more than once. Therefore, it can be concluded that the use of collaborative learning has been carried out based on the syntax of the implementation the collaborative learning method which abled to increased students’ reading skill.